Mr. Putter & Tabby : Turn the page - Rylant, Cynthia; Howard, Arthur (Boston : Houghton Mifflin Harcourt, 2014)
Mr. Putter and Mrs. Teaberry bring Tabby and Zeke to the library for a special storytime.
Booklist
Horn Book
School Library Journal
Booklist, November 2014
Christian Library, January 2015
Horn Book, April 2015
Keywords: Books and reading -- Juvenile fiction; Cats -- Juvenile fiction; Dogs -- Juvenile fiction; Libraries -- Juvenile fiction; Books and reading -- Fiction; Cats -- Fiction; Dogs -- Fiction; Libraries -- Fiction; Books and reading -- Fiction; Cats -- Fiction; Dogs -- Fiction; Libraries -- Fiction